ANALISIS PENDAPATAN DAN NILAI TAMBAH KEDELAI PADA USAHA PENGOLAHAN TAHU DI DESA MOTODUTO KECAMATAN BOLIYOHUTO KABUPATEN GORONTALO (STUDI KASUS INDUSTRI TAHU CIPTA SARI) - Mahmud, Sri Anggita; Imran, Supriyo; Moonti, Agustinus (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
This research aims to analyze the income earned by the tofu processing business and the added value of the tofu processing business in the Cipta Sari tofu industry in Motoduto village, Boliyohuto District, Gorontalo Regency. The data used in this research are primary data and secondary data, primary data obtained, and the results of direct interviews with the owner of the Cipta Sari tofu industry. Secondary data was obtained from several literature related to this research. In this research, the data analysis method used is the quantitative descriptive analysis method to analyze the income obtained by the Cipta Sari tofu industry and the Hayami method to analyze the added value of the soybeans in the tofu processing business. These results and research show that the income earned by the Cipta Sari tofu industry in one week of production is IDR. 7.666.907 resulting in an R/C ratio of 1,75 and the added value in one week of production has a ratio of 92,35% and is included in the high ratio because it is 92,35% ≥50% so it can be concluded that Cipta Sari’s tofu business is profitable for entrepreneurs and worthy of development.